Histopathological effects of electrosurgical interventions in an in vivo porcine model of colonic endoscopic mucosal resection. Issue 5 (25th June 2021) - Whitfield, Anthony M; Burgess, Nicholas G; Bahin, Farzan F; Kabir, Sharir; Pellisé, María; Sonson, Rebecca; Subramanian, Vishnu; Mahajan, Hema; McLeod, Duncan; Byth, Karen; Bourke, Michael J
Abstract : Objective: Endoscopic mucosal resection (EMR) in the colon has been widely adopted, but there is limited data on the histopathological effects of the differing electrosurgical currents (ESCs) used. We used an in vivo porcine model to compare the tissue effects of ESCs for snare resection and adjuvant margin ablation techniques. Design: Standardised EMR was performed by a single endoscopist in 12 pigs. Two intersecting 15 mm snare resections were performed. Resections were randomised 1:1 using either a microprocessor-controlled current (MCC) or low-power coagulating current (LPCC). The lateral margins of each defect were treated with either argon plasma coagulation (APC) or snare tip soft coagulation (STSC). Colons were surgically removed at 72 hours. Two specialist pathologists blinded to the intervention assessed the specimens. Results: 88 defects were analysed (median 7 per pig, median defect size 29×17 mm). For snare ESC effects, 156 tissue sections were assessed. LPCC was comparable to MCC for deep involvement of the colon wall. For margin ablation, 172 tissue sections were assessed. APC was comparable to STSC for deep involvement of the colon wall. Islands of preserved mucosa at the coagulated margin were more likely with APC compared with STSC (16% vs 5%, p=0.010). Conclusion: For snare resection, MCC and LPCC did not produce significantly different tissue effects. The submucosal injectate may protect the underlying tissue, and technique may more strongly dictate the depth and extent of final injury. For margin ablation, APC was less uniform and complete compared with STSC.